Kritik Pandangan G.H.A. Juynboll terhadap Ilmu al-Jarh wa al-Ta’dil - Arif Chasanul Muna (Universitas Darussalam Gontor, 2016)
The orientalist assumed that the method of ahl ḥadīts is only focused on the sanad analysis. Beyond that, they also give a critic of the sanad analysis methods and assume that is problematic. Among orientalists who discuss sanad is G.H.A. Juynboll. Besides, he agreed with his predecessors about the uncomprehensiveness method of ahl ḥadīts, Juynboll also argued that the aforementioned sanad analysis method. According to him, the science of al-jarḥ wa al-ta’dīl -which is the most important aspect in sanad analysis was deeply problematic, the reason can be traced from two sides; the first, the narrators (al-rāwi) assessment standards are not objective. The fact is, more assessments are based on the opposite (regionalism); it’s mean that in the early days of the hadith narration there were conflicts between one region to anothers, so that the narrators of the region refused to narrate from another regions. For example, the conflicts occurred between the narrators of Medina and Iraq or between Iraq and Syria. Secondly, a lot the terms have evolved over time, thus there occured various meanings among them. Therefore, through this article the writer will try to criticize this opinion and examine the level of Juynboll understanding to the methods of ahl ḥadīts analysis, especially on the issue of al-jarḥ wa al-ta‘dīl. Afterward, seeing to what extent the actual accuracy of the criticism is given by orientalist (in this case Juynboll) to the method of ahl ḥadīts.